2013
DOI: 10.1111/pce.12119
|View full text |Cite
|
Sign up to set email alerts
|

Putting mechanisms into crop production models

Abstract: Crop growth models dynamically simulate processes of C, N and water balance on daily or hourly time-steps to predict crop growth and development and at season-end, final yield. Their ability to integrate effects of genetics, environment and crop management have led to applications ranging from understanding gene function to predicting potential impacts of climate change. The history of crop models is reviewed briefly, and their level of mechanistic detail for assimilation and respiration, ranging from hourly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
152
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 189 publications
(158 citation statements)
references
References 170 publications
(214 reference statements)
4
152
0
2
Order By: Relevance
“…4), although the overall agreement across treatments was acceptable, keeping in mind the assumptions that had to be made when deriving the observation-based values. Likewise, growing-season green leaf [N], which together with LAI is essential for predicting photosynthesis (Boote et al, 2013), was also well reproduced (results not shown). By contrast, [C] as well as [N] in the dead leaf pool were either over-or underestimated (see Fig.…”
Section: Model Performance Fertiliser Trialsmentioning
confidence: 86%
See 4 more Smart Citations
“…4), although the overall agreement across treatments was acceptable, keeping in mind the assumptions that had to be made when deriving the observation-based values. Likewise, growing-season green leaf [N], which together with LAI is essential for predicting photosynthesis (Boote et al, 2013), was also well reproduced (results not shown). By contrast, [C] as well as [N] in the dead leaf pool were either over-or underestimated (see Fig.…”
Section: Model Performance Fertiliser Trialsmentioning
confidence: 86%
“…A mechanistic representation of the CO 2 response (as well as other processes) has been argued to be critical when modelling crop responses to climate change (Yin, 2013), as recently shown for state-of-the-art crop models (Boote et al, 2013). In contrast to crop models, which are optimised to simulate yields, DVMs are tools for exploring and predicting the coupled dynamics of ecosystem functioning, climate-carbon cycle interactions and biome distributions (Friedlingstein et al, 2013;McGuire et al, 2001;Prentice et al, 2007).…”
Section: S Olin Et Al: Yield and C : N Responses To N Management Anmentioning
confidence: 99%
See 3 more Smart Citations